1996
DOI: 10.1006/viro.1996.0220
|View full text |Cite
|
Sign up to set email alerts
|

Virus-like Particles of Bovine Papillomavirus Type 4 in Prophylactic and Therapeutic Immunization

Abstract: Virus-like particles were produced in insect cells containing either the L1 and L2 capsid proteins of bovine papillomavirus type 4 (BPV-4) or only the L1 protein. Both preparations of VLPs proved to be extremely effective prophylactic vaccines. Thirteen of 15 calves immunised with either L1-L2 VLPs or L1-VLPs were refractory to experimental challenge with high doses of BPV-4 and did not develop papillomas, while 9 of 10 control animals developed multiple oral papillomas. VLPs were not efficient as therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
165
0
5

Year Published

1998
1998
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 295 publications
(173 citation statements)
references
References 0 publications
3
165
0
5
Order By: Relevance
“…Prevention of BPV-4 infection by vaccination with L1-VLP shows that L1 by itself encodes neutralising antibodies. Vaccination with BPV-4 L1 and L2 or only L1-VLP efficiently prevents the development of experimentally induced papillomas, whereas its effect as a therapeutic mean against an established papillomas is equivocal [73].…”
Section: Immunity and Vaccinesmentioning
confidence: 99%
“…Prevention of BPV-4 infection by vaccination with L1-VLP shows that L1 by itself encodes neutralising antibodies. Vaccination with BPV-4 L1 and L2 or only L1-VLP efficiently prevents the development of experimentally induced papillomas, whereas its effect as a therapeutic mean against an established papillomas is equivocal [73].…”
Section: Immunity and Vaccinesmentioning
confidence: 99%
“…In 1996, Kirnbauer et al [58] first reported in a seminal study, that VLPs comprising the BPV-4 L1 and L2 or only the L1 protein triggered a strong humoural response in calves. This response led to immunity on a subsequent challenge with BPV-4, but did not induce papiloma regression in previously infected animals [52].…”
Section: Prophylactic and Therapeutic Vaccinesmentioning
confidence: 99%
“…VLPs are structurally and immunologically similar to infectious virus as gauged by electron microscopic imaging studies, and their ability to bind type-specific, conformation-dependent monoclonal antibodies (MAbs). Consequently, experimental vaccines have tested the efficacy of immunizing with VLPs in animal models of papillomaviruses (2,29,45) and in humans (19,32).…”
mentioning
confidence: 99%
“…Type-specific, conformation-dependent antibodies made in response to VLP vaccination do indeed protect animals against infectious viral challenge (27,29,45) and neutralize virus in in vitro assays (27). Protection against infection has been attributed to the humoral immune response since passive transfer of serum from immunized animals to untreated animals protects the recipient against infectious viral challenge (2).…”
mentioning
confidence: 99%